PO021 Adem triggered by toxic effect of synthetic cannabinoid, black mamba. (1st December 2017) - Samra, Kiran; Boon, Ian; Packer, Gregory; Abbas, Ahmed; Pucci, Mark; Reddy-Kolanu, Vinay; Ramalingam, Satheesh; Jacob, Saiju
Abstract : Acute disseminated encephalomyelitis (ADEM) is a multifocal demyelinating disease triggered by infection, vaccination or, as in this case, an exogenous toxin. Frequent manifestations include: fever, altered consciousness, seizures and MRI evidence at symptom onset of an extensive lesion load. This is a unique report of ADEM secondary to Black Mamba, which contains an endogenous cannabinoid receptor agonist, up to a hundred times as potent as delta-9-tetrahydrocannabinol, the active ingredient in cannabis. A previously well 25-year-old man presented with agitation, double incontinence and left-sided incoordination. Symptoms started after smoking Black Mamba five days earlier. Over 48 hours, he developed aphasia, generalised hypertonia, hyperreflexia and dense left hemiparesis. This progressed to profuse diaphoresis, pyrexia, tachycardia, hypertension and a possible seizure necessitating admission to the Intensive Care Unit. Computed tomography head and cerebrospinal fluid analysis were unremarkable. MR brain demonstrated multifocal hyperintense contrast enhancing lesions, which was suggestive of ADEM. An electroencephalogram showed widespread brain wave slowing, indicating diffuse cerebral dysfunction. Toxicology analysis of the substance confirmed a potent synthetic cannabinoid NM2201. The patient made a slow but significant recovery after a course of intravenous methylprednisolone, intravenous immunoglobulins and oral steroids, and is nearly back to his baseline nine months later.